Investigating the Influence on the Electro-Conductive Properties of Leather as a Result of Natural Aging - Majlinda Hylli; Aulon Shabani; Ilda Kazani; Genti Guxho (Textile & Leather Review, 2023)
Conductive leather and its use in smart products have found a lot of interest. Leather behaves as a good insulator, so it was treated with electrically conducting polypyrrole using a chemical polymerization technique to give it conductive characteristics. The electro-conductive properties are obtained by using the double in–situ oxidative polymerization of pyrrole. The electrical properties of conductive samples are studied using the Van Der Pauw method as a measuring method. The conductive leather transformation process was carried out during the 2018-2020 period, and the conductive leather samples were preserved in room conditions until the year 2023. The effect of natural ageing on the electro-conductive properties of conductive leather is the focus of this research. The results show that environmental factors influence polymer breakdown and stability, by causing an increase in electrical resistance. The changes in electrical surface resistance, as the effect of the ageing factor, vary from 39.8% to 129.9%. Those changes in electrical resistance indicate that ageing is one of the major concerns in the electrical properties and stability of conductive leather samples, so the performed measurements have importance in providing information for the researchers and designers regarding the conductivity changes over time as a result of natural ageing, which would like to work with conductive leather on smart products.